POVM construction: a simple recipe with applications to symmetric states - Sirsi, Swarnamala; Bharath, Karthik; Shilpashree, S.P.; Rao, H.S. Smitha (World Scientific Publishing, 2017)
We propose a simple method for constructing POVMs using any set of matrices which form an orthonormal basis for the space of complex matrices. Considering the orthonormal set of irreducible spherical tensors, we examine the properties of the construction on the n+1-dimensional subspace of the 2n-dimensional Hilbert space of n qubits comprising the permutationally symmetric states. Using the notion of vectorization, the constructed POVMs are interpretable as projection operators in a higher-dimensional space. We then describe a method to physically realize the constructed POVMs for symmetric states using the Clebsch-Gordan decomposition of the tensor product of irreducible representations of the rotation group. We illustrate the proposed construction on a spin-1 system, and show that it is possible to generate entangled states from separable ones.